1958
DOI: 10.1111/j.2042-7158.1958.tb10398.x
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Purgatives Containing Anthracene Derivatives

Abstract: Evidence is produced to show that the sennosides are probably breakdown products from primary glycosidal compounds occurring in the crude drug. Carefully prepared extracts have been shown to contain these primary compounds and one such compound has been isolated in a pure form. Biological and chemical assays show it is about 50 per cent more active than the sennosides and the relation of this fact to the explanation of the total activity of senna is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1960
1960
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The cascarosides are probably the most important components. In preliminary experiments we have found them more active biologically than the aloins, which is consistent with the fact that the primary glycosides of senna are more active than the secondary ones (Fairbairn, Friedmann & Ryan, 1958). Furthermore they have a sweet taste in contrast to the aloins, and are therefore preferable pharmaceutically.…”
supporting
confidence: 84%
“…The cascarosides are probably the most important components. In preliminary experiments we have found them more active biologically than the aloins, which is consistent with the fact that the primary glycosides of senna are more active than the secondary ones (Fairbairn, Friedmann & Ryan, 1958). Furthermore they have a sweet taste in contrast to the aloins, and are therefore preferable pharmaceutically.…”
supporting
confidence: 84%
“…Pods are hung in bunches in well ventilated shade conditions for I 0-12 days to dry. If stored properly and protected from light, senna leaves, pods or their powder retain their biological activity even after five years (Fairbairn et al 1958). The crop yields 1400 kg of leaves and about 150 kg of pods ha-1 under irrigated conditions; yield under unirrigated conditions is lower, ranging from 500-600 kg of leaves and 80-100 kg of pods (Husain 1992).…”
Section: Harvesting and Yieldmentioning
confidence: 98%
“…The two compounds are emodin 1 (or 8) glucoside sul phate and emodin dianthrone diglucoside sul phate; under very mild acid hydrolysis condi tions they produce the corresponding normal glycosides by loss of sulphate. Fairbairn et al (1958) isolated a glycoside from senna which had an equivalent weight of 620 (sennosides 432) an estimated molecular weight of 1,164 (sennosides 862) and which on mild hydrolysis produced sennoside equivalent to 74% of the original substance. Later work showed that four glucose molecules were present and for convenience we refer to this as P4.…”
Section: Sulphated Glycosidesmentioning
confidence: 99%